2009
DOI: 10.1248/cpb.57.421
|View full text |Cite
|
Sign up to set email alerts
|

Euscaphinin, a New Ellagitannin Dimer from Euscaphis japonica (THUNB.) KANITZ

Abstract: NotesRecent studies on plant polyphenols have revealed various biological activities for ellagitannins.1,2) Distribution of ellagitannins in plants is relatively limited compared with that of condensed tannins (proanthocyanidins).3) In this study, we proposed to find new plant sources of functional polyphenols and examined the leaves, bark and wood of 39 plant samples belonging to 32 genera of 29 families, distributed in the Nagasaki region of Japan, by thin-layer chromatography (TLC) and high performance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Peak 3 yielded a [M-H]ion at m/z 447 (corresponding to an aglycone) and a major fragment ion at m/z 284 due to the loss of a hexose unit, and was identified as kaempferol-3-O-glucoside. These results were confirmed by comparisons with MS data in previous reports [63][64][65]. Previous studies showed that flavonoids quercetin-3-O-glucuronide and kaempferol-3-O-glucoside exhibited antibacterial activity by reducing the fluidity of the inner and outer layers of bacterial membranes, inhibiting DNA and RNA synthesis, and deterring energy metabolism [66].…”
Section: Type Of Bacteriasupporting
confidence: 85%
“…Peak 3 yielded a [M-H]ion at m/z 447 (corresponding to an aglycone) and a major fragment ion at m/z 284 due to the loss of a hexose unit, and was identified as kaempferol-3-O-glucoside. These results were confirmed by comparisons with MS data in previous reports [63][64][65]. Previous studies showed that flavonoids quercetin-3-O-glucuronide and kaempferol-3-O-glucoside exhibited antibacterial activity by reducing the fluidity of the inner and outer layers of bacterial membranes, inhibiting DNA and RNA synthesis, and deterring energy metabolism [66].…”
Section: Type Of Bacteriasupporting
confidence: 85%
“…NMR data for these compounds were completely the same to previous reports [10][11][12][13][14][15][16][17].…”
Section: Extraction Of Plant Materialssupporting
confidence: 77%
“…1) [10][11][12][13][14][15][16][17]. Among the isolated compounds, 2 and 3 were identified as a/b(3/2)-punicalagin (2) and a/b(3/2)-terchebulin (3).…”
Section: Isolation and Identification T Brownii Bark Meoh Extract Comentioning
confidence: 99%
“…Euscaphis has been widely used in traditional Chinese medicine. Several chemical compounds have been isolated from Euscaphis , such as triterpene compounds [ 26 29 ], phenolic acid compounds [ 30 , 31 ], flavonoid compounds [ 27 , 31 ] and others [ 31 33 ], however, no molecular and gene expression data has been reported in Euscaphis .…”
Section: Introductionmentioning
confidence: 99%